Cities under water flood prevention in the mirror of early modern municipal media - Wüst, Wolfgang (Biuletyn Polskiej Misji Historycznej = Bulletin der Polnischen Historischen Mission, 2019)
There are numerous sources concerning the issue of the flood disasters in cities located on rivers in early modern in southern Germany, such as municipal chronicles, annals, reports, journals, leaflets, decrees, regulations and water police ordinances. What is striking is that natural disasters were interpreted by people of the period as the “anger of God”. However, from the 18th century, there were also hypotheses and scientific solutions to the issue of flood prevention.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Deluges; Floods; Memories of the flood; Nuremberg; Water police